Niosomes and liposomes as promising carriers for dermal delivery of Annona squamosa extract (Brazilian Journal of Pharmaceutical Sciences, 2020)
The leaf extract of Annona squamosa L. has antibacterial, antidiabetic, antioxidant, and anticancerous activities. The present work aims to compare between liposomes and niosomes as carriers for A. squamosa extract to improve its transdermal bioavailability. Physical characterization for niosomes and liposomes was performed using: transmission electron microscope (TEM), scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FTIR). In addition, the encapsulation efficiency for A. squamosa in both carriers was evaluated and in-vitro drug release experiments were performed. The results proved the potential of both carriers to penetrate the outer layer of the skin (stratum corneum) which is considered as a strong barrier against the diffusion of many compounds through the skin. Moreover, the results pointed out that niosomes and liposomes lasted long time through the skin, which ensures the presence of antioxidant extract in the skin for prolonged periods. This would have a benefit of targeting free radicals in the skin. The encapsulation efficiency of liposomes for A. squamosa extract exceeded that of niosomes, however, niosomes demonstrated longer time of drug release through the skin. In conclusion, niosomes and liposomes are promising carriers for dermal delivery of the antioxidant extract Annona squamosa.